The particle image tracking technique: An accurate optical method for measuring individual kinematics of rigid particles. (29th June 2020) - Richefeu, Vincent; Combe, Gaël
Abstract: We present a new approach to assess the two‐dimensional motion of rigid bodies in granular materials. Although it was adapted from digital image correlation technique, the heart of the presented technique relies on specific treatments related to the discrete nature of grain‐displacement fields. The code called Tracker has been developed to process the digital images and measure the in‐plane displacement and rotation of each individual grain from one image to another. A remarkable feature is the use of a specific strategy that allows tracking all particles, without losing any of them (which is a typical problem when tracking assemblies of discrete particles over many images). This is achieved by a two‐step procedure, where, in case of problematic tracking of a grain, the size of the search zone is increased in an adaptive manner, that is, taking into account the results of tracking in the neighbourhood of the particle. The accuracy of the measured displacements and rotations was tested on both perfect synthetic images and digital photographs of a sheared assembly of grains. An automatic procedure that corrects the lens distortion further improves the quality of the measurements. The accurate assessment of the grain kinematics opens very interesting perspectives, especially in the study of displacement fluctuations in granular media.